Transposable elements are dysregulated in brains of individuals with major depressive disorder - Truby, Natalie L.; Smith, Corinne; Hamilton, Peter J. (Journal of affective disorders, 2026)
Transposable elements (TEs) are repetitive DNA sequences capable of being transcribed and re-integrated, or transposed, into distinct loci throughout the genome. While thought to be largely transcriptionally silenced in brain, TE transcription is increasingly recognized as dynamic and involved in human health and disease states, including in disorders of the brain. In this study, we annotated TE transcripts in publicly available RNA sequencing (RNAseq) of postmortem human brain tissue to investigate the expression profile of TE transcripts in individuals with major depressive disorder (MDD) compared to healthy controls. Our findings reveal a robust impact to TE transcript expression in the brains of subjects with MDD relative to controls. This work points to the aberrant transcription of cortical TEs as a potentially overlooked molecular signature of MDD. •TE transcripts are uniformly downregulated in the brains of people with MDD.•TEs localized within introns of adaptive immune genes are particularly affected.•MDD-associated TE dysregulation is differentially affected by brain region and cell type.•MDD alters the natural sex and age differences in brain TE expression.